U Uji Aktivitas Antibakteri Ekstrak Daun Pulutan (Urena lobata L) Terhadap Bakteri Streptococcus pyogenes - Pusvita, Shela; Rohama, Rohama; Yuwindry, Iwan; Darsono, Putri Vidiasari (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: Pharyngitis or sore throat has a fairly high prevalence rate in Indonesia caused by Streptococcus pyogenes bacteria. Pulutan has experience as a medicine for sore throat, rheumatic fever, antipyretic, fracture, antifertility, and vaginal discharge. Based on research on ethanol extract that was done previously, pulutan leaf extract has antibacterial activity. Objective: To determine the antibacterial activity of pulutan leaf extract (Urena lobata L) which has the potential as an antibacterial against the growth of Streptococcus pyogenes and to determine the minimum inhibitory concentration and minimum killing concentration. Methods: This type of true experimental research design, namely research methods that look for causal relationships between independent and dependent variables. Antibacterial testing using disc diffusion and dilution methods. With concentrations of 100%, 75%, 50%, 25%, positive control amoxicillin and DMSO negative control. Results: The results of the disc diffusion test were able to inhibit the growth of the Streptococcus pyogenes bacteria which was indicated by the presence of a clear zone around the disc paper. The results of the dilution test obtained the MIC value at a concentration of 50% indicated by the media tube which looks clear. There was no KBM value at all the concentrations of the extracts tested, indicated by the growth of bacteria in the test medium. Conclusion: Pulutan leaf extract (Urena lobata L) has antibacterial activity which is indicated by the presence of an inhibition/clear zone around the disc paper. MIC results found at a concentration of 50%, KBM results on pulutan leaf extract (Urena lobata L) did not have killing power at all concentrations. Keywords: Antibacterial, Pulutan Leaf Extract (Urena lobata L), Streptococcus pyogenes.